New or Persistent Right Ventricular Systolic Dysfunction Is Associated With Worse Outcomes in Pediatric Acute Respiratory Distress Syndrome. Issue 2 (February 2020) - Himebauch, Adam S.; Yehya, Nadir; Wang, Yan; McGowan, Francis X.; Mercer-Rosa, Laura
Abstract : Objectives: The trajectory and importance of right ventricular systolic function and pulmonary hypertension during the course of pediatric acute respiratory distress syndrome are unknown. We hypothesized that new or persistent right ventricular systolic dysfunction and pulmonary hypertension would be associated with worse patient outcomes. Design: Retrospective, single-center cohort study. Setting: Tertiary care, university-affiliated PICU. Patients: Children who had at least two echocardiograms less than 8 days following pediatric acute respiratory distress syndrome diagnosis. Interventions: None. Measurements and Main Results: Between July 1, 2012, and April 30, 2018, 74 children met inclusion criteria. The first echocardiogram was performed a median of 0.61 days (interquartile range, 0.36–0.94 d) and the second echocardiogram was performed a median of 2.57 days (interquartile range, 1.67–3.63 d) after pediatric acute respiratory distress syndrome diagnosis. Univariate analyses showed that new or persistent right ventricular systolic dysfunction as defined by global longitudinal strain or free wall strain was associated with a greater number of ICU days in survivors (global longitudinal strain p = 0.04, free wall strain p = 0.04), lower ventilator-free days at 28 days (global longitudinal strain p = 0.03, free wall strain p = 0.01), and higher rate of PICU death (global longitudinal strain p = 0.046, free wall strain p = 0.01). Mixed-effects multivariate modeling showed that right ventricular global longitudinal strain and right ventricular fractional area change stayed relatively constant over the course of the first 8 days in nonsurvivors and that there was a linear improvement in global longitudinal strain ( p = 0.037) and fractional area change ( p = 0.05) in survivors. Worsening right ventricular dysfunction at the time of repeat echocardiogram as defined by global longitudinal strain and free wall strain were independently associated with decreased probability of extubation (subdistribution hazard ratio, 0.30 [0.14–0.67]; p = 0.003 and subdistribution hazard ratio, 0.47 [0.23–0.98]; p = 0.043, respectively). In univariate and multivariate analyses, pulmonary hypertension had no significant associations with outcomes in his cohort. Conclusions: New or persistent right ventricular systolic dysfunction over the first week following pediatric acute respiratory distress syndrome onset is associated with worse patient outcomes, including decreased probability of extubation and higher PICU mortality. Abstract : Supplemental Digital Content is available in the text.